Bioleaching of copper from chalcopyrite ore at higher NaCl concentrations. (1st January 2022) - Behrad Vakylabad, Ali; Nazari, Sabereh; Darezereshki, Esmaeel
Highlights: Processing low-grade chalcopyrite ore (<0.3% Cu) is the main challenge of copper complexes. Controlling jarosite makes the process attractive from technical and economical viewpoints. Two main strategies were studied: ORP control and chloride addition in irrigation. A hybrid lixiviant (Sulfate-chloride) resulted in more than 80% copper recovery by ore bioleaching. Abstract: The formation of hydrolyzed ferric iron (Fe (III)) as jarosite could limit the bioleaching of copper and significantly lower the dissolution rate of low-grade chalcopyrite ore. Thus, to improve the rate through overcoming the hindered dissolution of chalcopyrite, this study investigated the influence of chloride addition into leaching lixiviant. As a microbial source, mixed mesophiles, moderately thermophilic, and thermophilic microorganisms were adapted to about 120 mM NaCl solution. After optimization of the ore bioleaching in 64 controlled mini-columns, the scaled tests in 2-m tall columns were conducted to study the overall leaching procedure and precipitation of the jarosite. Under normal aeration conditions (0.05 Nm 3 /m 2 /h) with hybrid irrigation (120 mM NaCl in H2 SO4 solution at pH = 1.5), copper recovery reached 80% after 120 days while it was approximately 50% with limited one (0.003 Nm 3 /m 2 /h). The limited aeration column had a moderate oxidation–reduction potential (ORP) with values < 450 mV. This significant improvement in dissolution is explained by the reduced precipitation of passivating layer (mainly jarosite). These conclusions were also confirmed by the estimation of pyrite and natrojarosite with a modified ASTM D-2492 (MASTM D-2492). Moreover, to identify the microbial communities in the columns, DNA extraction and 16Sr RNA gene PCR amplification and sequencing were done.